Analisis Yuridis Fungsi Hukum Waris dalam KUHPerdata Terhadap Tindakan Penjualan Harta Warisan Secara Sepihak Oleh Salah Satu Ahli Waris - Rayi Kharisma Rajib; Nadya Agustina; Dias Mutik Rahayu (CV. KAMPUS AKADEMIK PUBLISING, 2026)
. Inheritance disputes often trigger family conflicts, particularly when one heir unilaterally sells inherited property without the consent of other heirs. This study aims to analyze the regulation of inheritance law in the Indonesian Civil Code (KUHPerdata) regarding such actions and to examine its function in resolving disputes among heirs. The research uses a normative legal method with a statutory approach. The results indicate that under KUHPerdata, an undistributed estate is considered jointly owned by all heirs and therefore cannot be transferred or sold unilaterally. Such actions may be classified as unlawful acts and have the potential to cause disputes. Thus, inheritance law in KUHPerdata plays an important role in providing legal certainty and serves as a mechanism for resolving conflicts to protect the rights of all heirs.